A Case Series of Penile Skin Grafting in Children - Qiu, Lin; Zhang, Xuan; Liu, Yan; Fu, Yuexian; Yuan, Xingang (European Journal of Pediatric Surgery Reports, 2020)
Pediatric penile skin grafting is rarely performed. We present a case series of four pediatric patients receiving skin grafting due to the loss of penile skin. The four boys were followed up for 1 to 5 years. One full-thickness skin graft and three split-thickness skin grafts (STSGs) survived well with low Vancouver scar scale scores. One boy gradually developed lymphedema of the distal foreskin and underwent a second preputioplasty. He presented with normal erectile function and did not experience any pain. We propose thick STSGs as the most appropriate choice for pediatric penile skin reconstruction. Lymphedema of the foreskin is an important long-term complication of penile skin grafting.
Keywords: pediatric; penis; skin grafts; lymphedema